Unlocking Potential: Mapping Arabic Student Theses to Innovate Inter-Departmental Exchange Programs - Dolla Sobari; Kristina Imron; Yahya Abdullah; Salwa Humairoh; Nadya Syafira Putri (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study aimed to map the trends of thesis topics and research methods used by students of the Arabic Language Education (PBA) and Arabic Literature (BSA) programs at the Islamic State University of Raden Fatah Palembang during 2020–2021. Using a quantitative method with frequency distribution analysis, data were collected from 80 PBA theses and 46 BSA theses written in Arabic. The results showed that PBA students focus on pedagogical components (63%), Arabic language skills (22%), and Arabic linguistics (15%). In contrast, BSA students mainly explored linguistic topics (72%), followed by literature (17%) and Arabic language studies (11%). While PBA students employed varied research methods, BSA students consistently used qualitative descriptive approaches. This study contributes to Arabic language education by highlighting thematic patterns and methodological trends, offering a strategic foundation for interdepartmental curriculum development and academic collaboration between the PBA and BSA programs in Islamic State University of Raden Fatah.